Análisis de la incidencia del microcrédito en la creación de microempresas en la parroquia Alamor, del cantón Puyango de la provincia de Loja, en el año 2011 y propuesta de implementación de un programa de microcrédito rural como herramienta de desarrollo - Castillo Jaramillo, Camilo Víctor (2016)
The thesis entitled "analysis of the impact of microcredit in the creation of micro ALAMOR PARISH, THE PUYANGO of Loja province Canton in 2011 and proposal to implement a microcredit program AS A TOOL FOR RURAL DEVELOPMENT"; he was made for the purpose of contributing to improving the income levels and living conditions of its inhabitants, through the injection of working capital to improve production capacity and launching small businesses. He met the objectives; for which he was left with physical observation of the Canton Puyango, then with gathering information about the theoretical contents of microcredit and program models of savings and credit to encourage microcredit, besides the application of surveys performed to Village economically Active Puyango Canton, to meet adequately the current situation in Canton and receiving financial support to encourage the productive development of their inhabitants. After systematize information, the proposal for the implementation of a rural microcredit program for Puyango Canton, the same that allow communities to establish their own credit and savings associations, providing the opportunity for these sectors to accumulate and manage develops means; providing loans with joint liability and promoting savings. With the implementation and proper administration of the Communal Bank it can demonstrate that small producers are reliable for the return of financial resources and that they improve the quality and living conditions of their families.